Nano-TiO2/MWCNT composite coating with high DC flashover strength and super hydrophobicity. (1st March 2023) - Liu, Xi-Ying; Yao, Hai-Bin; Jiang, Tao; Zhu, Chen; Song, Da-Wei; Liu, Zong-Jie; Xu, Guo-Qiang; Wang, Cheng-Quan; Li, Bin; Song, Wei-Ting; Qi, Xiao-Wu
Abstract: Epoxy resin (EP) materials are frequently used in high voltage power equipment because of their excellent electricity, force, and heat properties. However, under the condition of DC high voltage, the surface of EP insulation material is more likely to accumulate charge, which distorts the nearby electric field and causes flashover along the surface. In this article, a nanocomposite coating was prepared by spraying through the nanoparticles (TiO2 with carbon nanotubes) dispersed in the polydimethylsiloxane (PDMS) elastomers solution. Micro-nano porous structures are introduced in the spraying process, which hinders the development of collision ionization and increases the flashover strength of the coating. At the same time, the change in surface morphology makes the hydrophobic properties of the coating improve and enhances the anti-icing and anti-fouling capacity. Spraying nano filler provides a general method for improving hydrophobicity and flashover strength.